Using Participatory Design to Develop Communication-Supporting Technology: A Scoping Review - Ansari, Rafiah; Anvari, Soraya; Escobedo, Lizbeth; Wehbe, Rina R. (Anais da Conferência Latino-Americana de Interação Humano-Computador (CLIHC); 2026: Anais da XII Conferência Latino-Americana de Interação Humano-ComputadorDO - 10.5753/clihc.2026.20411, 2026)
Building on and updating foundational reviews from a decade ago, this scoping review synthesizes Participatory Design (PD) practices in the design of communication support systems for neurodivergent children. Focus is given to interdisciplinary frameworks, technological outputs, and the reported experiences of children engaged in the process via PD. Findings indicate the emergence of bespoke PD methods informed by a complex interplay between child development and computer science. Children’s experience of PD and technology impact are dependent on individual capability and access to support networks. Most tools are designed for remediation, at times incorporating playfulness and gamification for sustained motivation. Future work should prioritize participant diversity, provide transparency in reporting theoretical foundations, and incorporate robust validation of design outputs.